Peningkatan Kompetensi Guru melalui Program Pengabdian Masyarakat dalam Rangka Mewujudkan Pendidikan Inklusif di Tk PKK Sahang - Dewi Rahmawati; Fitri Wahyuni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to describe the efforts in implementing inclusive learning at TK PKK Sahang as a form of commitment to providing equal educational services for all children, including children with special needs. The research method used is, a) descriptive qualitative, with data collection techniques through b) observation, c) interviews, and d) documentation. The results of the study indicate that TK PKK Sahang has made various efforts to create an inclusive learning environment, including providing teacher training, adjusting the curriculum, offering diverse learning media, and building effective communication with parents. However, the implementation of inclusive learning still faces challenges, such as limited human resources and supporting facilities. In conclusion, TK PKK Sahang has shown a strong commitment to implementing inclusive learning, although continued support from various parties is needed to optimize its implementation.